Plasticity of Brain Networks in a Randomized Intervention Trial of Exercise Training in Older Adults - Voss, Michelle W.; Prakash, Ruchika S.; Erickson, Kirk I.; Basak, Chandramallika; Chaddock, Laura; Kim, Jennifer S.; Alves, Heloisa; Heo, Susie; Szabo, Amanda; White, Siobhan M.; Wojcicki, Thomas R.; Mailey, Emily L.; et al. (Frontiers in Aging Neuroscience, 2010)
Research has shown the human brain is organized into separable functional networks during rest and varied states of cognition, and that aging is associated with specific network dysfunctions. The present study used functional magnetic resonance imaging (fMRI) to examine low-frequency (.008<.08 Hz) coherence of cognitively relevant and sensory brain networks in older adults who participated in a one-year intervention trial, comparing the effects of aerobic and non-aerobic fitness training on brain function and cognition. Results showed that aerobic training improved the aging brain’s resting functional efficiency in higher-level cognitive networks. One year of walking increased functional connectivity between aspects of the frontal, posterior, and temporal cortices within the Default Mode Network and a Frontal Executive Network, two brain networks central to brain dysfunction in aging. Length of training was also an important factor. Effects in favor of the walking group were observed only after 12 months of training, compared to non-significant trends after six months. A non-aerobic stretching and toning group also showed increased functional connectivity in the DMN after six months and in a Frontal Parietal Network after 12 months, possibly reflecting experience-dependent plasticity. Finally, we found that changes in functional connectivity were behaviorally relevant. Increased functional connectivity was associated with greater improvement in executive function. Therefore the study provides the first evidence for exercise-induced functional plasticity in large-scale brain systems in the aging brain, using functional connectivity techniques, and offers new insight into the role of aerobic fitness in attenuating age-related brain dysfunction.